Tuberculous peritonitis: experience in a community hospital - da Fonseca, Leonardo Gomes; de Campos, Fernando Peixoto Ferraz; Felipe-Silva, Aloísio (Autopsy and Case Reports, 2011)
Peritoneal tuberculosis presents high morbi-mortality rates and its prognosis depends on early diagnosis. Symptoms mimic other abdominal diseases, what makes diagnosis difficult. We report clinical and pathological data from 10 tuberculous peritonitis patients admitted to Hospital Hospital Universitário da Universidade de São Paulo between 2003 and 2010. Abdominal pain, fever and weight loss were the most frequentsymptoms and ascites was observed in half of cases. The serum-ascites albumin gradient determination and adenosine deaminase activity helped to make the diagnosis.Culture growth of Mycobacterium tuberculosis showed low sensitivity. The finding of chronic granulomatous serositis and positive stain for acid fast bacilli in biopsy specimensobtained from laparotomy and laparoscopy were determinant for diagnosis.